Performance of solar air-conditioning system using heat pipe evacuated tube collector - Mahendran, Moorthy (2010)
This is a study on the performance of solar air-conditioning system using heat pipe evacuated tube collector. The objective of this project is to analysis the performance solar air-conditioning system by determining the solar collector efficiency, coefficient of performance (COP) of the absorption chiller, and overall system efficiency and also the electrical energy consumption and operation cost for the system and compare it with the conventional air-conditioning system from the previous case study. The existing solar air-conditioning system is not competitive with electricity driven air-conditioning system because of their high investment and installation cost. Its overall thermal energy conversion efficiency is relatively low, and from an economical point of view, solar cooling and refrigeration are not competitive with the conventional systems. The experiment is conducted at Solar District Cooling Sdn. Bhd and data collected from building automation system for 30 days from 1st-30th June 2010. The data analysed using the theoretical analysis and plotted in graph to discuss about it. The solar collector efficiency varies from 50 to 80% during day time and stored energy can be used during night time. The COP varies from 2.961-2.966 and the overall system efficiency is from 30 to 50%. The investment cost is higher and electrical consumption is relatively lower than conventional air-conditioning system. The economical view is profitable after 18 years and 7 months of installation and environmental view is green energy without pollution. Although all the above findings refer to a particular application in Malaysia, the similar results can be obtained in the country with high solar availability. Finally by considering the problem of pollution of the planet due to the burning of fossil fuels the adoption of solar energy to power absorption chillers, even with marginal economic benefits, should not be underestimated.